Long-term evaluation of the Grassmaster II probe to estimate productivity of pastures - Serrano, João (2020)
The standard method of assessing pasture biomass is based on cutting the forage and requires great effort and expense to collect enough samples to accurately represent a pasture. This work presents the results of tests carried out to calibrate a capacitance probe (Grassmaster II). A monthly regression analysis was performed between the capacitance (CMR) measured by the probe and the values of pasture green matter and dry matter (respectively, GM and DM, in kg ha-1). The results showed that the more favorable period for the use of this probe in dry land pastures in Alentejo Portuguese region coincides with the end of winter and beginning of spring (February-March). It can be concluded that the capacitance probe is an expedient tool that can enable the farm manager to estimate pasture productivity and support the decision-making process in the management of dry land pasture and its respective grazing.